The habilitation of mentally retarded adults - Gilbert, Patricia Jane (Department of Pathology, 2024)
The history of the care of the mentally retarded in Western civilization is outlined including the care of the mentally retarded in South Africa. Difficulties in the definition and assessment of mental retardation are indicated and problems in present day institutional care are considered: specific reference is made to the characteristics of institutionalization and to the role of institutions in the future. Pre-discharge training within the institutional setting is discussed with particular emphasis on the curriculum of such training programmes training methods. and the role of transitional facilities. This is followed by a critical review of prognostic and follow up studies of retarded persons discharged into the community, and a consideration of the concepts of "success" and "normalization". An experimental study was conducted to evaluate the specific training programme (ASAT) in operation at Fernhill Care and Rehabilitation Centre. The degree of improvement shown after six months by those participating in the programme was compared with a control group. The experimental and control groups were matched on age, IQ and length of institutionalization. The living skills of the mentally retarded subjects were assessed on the ten areas covered by the ASAT Schedules an assessment procedure previously designed for the assessment of such skills. Significant improvement was found in the two areas of finance and measurement only, and no clear trends emerged relating either age, IQ or length of institutionalization to the degree of improvement shown. Possible reasons for the lack of measured improvement in the other areas of skills are outlined. The need for systematic revision of the assessment procedure itself is indicated and the possible effects of the institutional environment upon the retention and learning of skills is discussed. Recommendations for increasing the efficacy of the training programme within the institutional setting are put forward and suggestions are made for easing the transition from institutional to community living. A detailed investigation of the lives of discharged persons already living in the community was carried out to assess the suitability of the content of the ASAT programme as a preparation for discharge. It was found that none of the subjects was living completely independently and that this was largely due to the restricting circumstances in which they had been placed, rather than lack of potential. The content of the training programme was found to be relevant to community life except for the omission of training in employment practices and the use of leisure time. It is suggested that greater consideration be given to the achievement of maximum levels of functioning for those discharged rather than simply being discharged into "protective" settings. It is concluded that many mentally retarded persons are well able to speak for themselves and that greater effort should be made to ascertain their views.